2015 48th Hawaii International Conference on System Sciences 2015
DOI: 10.1109/hicss.2015.234
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Social Media Skills Trainer for Vocational Education and Training: Concept and Implementation of a Recommender System

Abstract: The use of social media in the private and professional context is continuously increasing. Particularly in the private context most users are competent in dealing with these technologies. However, when it comes to apply social media in the professional context (e.g. communicating or searching for relevant information or integrating social media in classes or the preparation of homework), most users still show a lack of competencies. Thus, students and teachers would benefit from tailored access to online educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The objective of the study proposed by [25] was the development of social media skills based on whether users had or lacked these skills. Our proposal not only works with the skills obtained by a user in their academic background or in the course of their job, but also considers their current position and related ones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The objective of the study proposed by [25] was the development of social media skills based on whether users had or lacked these skills. Our proposal not only works with the skills obtained by a user in their academic background or in the course of their job, but also considers their current position and related ones.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature on the use of ontologies for RSs highlights the importance of information representation and management. The study by [25] indicated that the amount of information handled is a key factor for recommendations to be successful and proposed that future studies could do tests with real data in order to have a sufficient sample size.…”
Section: Related Studiesmentioning
confidence: 99%
“…By recommending appropriate apprenticeship location, students will maximally develop their own skills in the industrialized world. There is a recommendation system developed with adaptive methods of using social media to develop individual skills [17]. Research on the use of online forums to develop student skills in apprenticeships [18], then to support the competency of the apprentice participants is done by developing a Portal [10].…”
Section: Discussionmentioning
confidence: 99%
“…In this review, the importance of the representation and management of information is highlighted. Studies [10,11] pointed out that ontologies allow information of interest to users to be inferred, which can be used to enrich recommendations. Likewise, [12] indicated that the amount of information handled is a key factor in the success of recommendations.…”
Section: Introduction and Related Studiesmentioning
confidence: 99%